PELATIHAN KETERAMPILAN DESAIN RUANGAN KELAS PAUD UNTUK PERKEMBANGAN EMOSIONAL ANAK USIA DINI DENGAN METODE KAIZEN - Ranti Mustika Putri; Evi Desmariani; Muzayyanah Muzayyanah; Elvina Rahayu (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
One of the current phenomena is the limited ability of PAUD teachers in designing the interiors of PAUD classrooms and the lack of Educational Game Tools. This causes the child to create a pleasant atmosphere for himself by showing emotional behaviors that do not have empathy for the teacher who is teaching and friends who are following the lesson. Therefore, knowledge and skills of teachers are needed in designing the room. One method that can be used to help make interior design more effective is to use the Kaizen method which is defined as continious improvement. Community service activities in the form of skills training with lecture methods and direct practice. The interior design in each PAUD classroom is given for attic, wall and floor elements based on character values. The learning atmosphere, especially for early childhood, will be safe, comfortable and fun so that the emotional problems that are often encountered in children will be resolved.